Nnnnxx5 Deep Learning Assisted Hi-Tech Farming Framework - Aswini.J, Dr.N.Malarvizhi (International Journal of Advanced Science and Technology, 2020)
Agriculture is vital for all. With the continual advances in technologies, there is an increased demand for smart farming. Deep Learning applications in agriculture and advanced farming is trend in recent research. Research in this area is of great interest and with a very active research community. This paper proposed a Hi-Tech farming with deep learning. The method used in the proposed system is a recent development with Deep Learning and Internet of Things (IOT) which is agreeable the agriculture in an well-organized way as well as to increase the income of the villagers by smart farming with the existing minimum lands of farmers. Without investing much on the existing infrastructure and also the land procured by them is sufficient to implement this proposal.